FINANCIAL SUSTAINABILITY RESEARCH TREND: BIBLIOMETRICS AND CONTENT ANALYSIS - Kustina, Ketut Tanti; Tirtayani, I Gusti Ayu (Erudio Journal of Educational Innovation, 2026)
This paper comprehensively analyzes financial sustainability studies conducted over the past six years.   A comprehensive synthesis is essential due to the fragmented literature on financial sustainability.   This study aims to address the existing gap in knowledge by compiling a comprehensive collection of published material in the form of an annotated bibliography on financial sustainability.   Furthermore, it accounts for the most recent research developments within the past six years and the specific subject areas addressed.   The researchers utilize the bibliometric analysis method and VOSviewer to depict the study on financial sustainability spanning from 2018 to 2023.   We obtained the data from the Scopus database.   The study's findings reveal the existence of sixteen distinct research clusters that have emerged over the past ten years. These clusters are identified explicitly as (1) Sustainability, (2) operational efficiency, (3) social entrepreneurship, (4) financial sustainability, (5)company growth, (6) financial performance, (7) good financial governance, (8) good stability, good governance, (9) capital investment,(10)  risk governance,(11) capital investment, (12) publicly traded, (13) the credit growth, (14) intellectual capital, (15) revenue diversification,  (16) reverse mortgage. There are several research variables discussed in the latest period related to financial sustainability. The variables are financial inclusion, digital financial service, financial service digitability, intellectual capital, fiscal policy, innovation, capital investment, good financial governance, risk governance, and risk management. Archives, experiments, and surveys have dominated the research methods used during the last six years. This study offers a comprehensive examination for students and academics interested in researching the financial sustainability of many issues. It covers the topics, concepts, and research methods that have been used in recent years and are still being used.